2022
DOI: 10.3389/fphys.2022.912126
|View full text |Cite
|
Sign up to set email alerts
|

Changes of repolarization parameters after left bundle branch area pacing and the association with echocardiographic response in heart failure patients

Abstract: Background: Left bundle branch area pacing (LBBAP) has become a safe and effective option for heart failure (HF) patients indicated for cardiac resynchronization therapy (CRT) and/or ventricular pacing, yet the response rate was only 70%. Repolarization parameters were demonstrated to be associated with cardiac mechanics and systolic function. This study aimed to investigate the effects of LBBAP on repolarization parameters and the potential association between those parameters and echocardiographic response.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…A prolonged TpTe interval and TpTe/QT ratio have been shown to be associated with arrhythmogenesis and sudden cardiac death 30 . LBBP‐CRT has been shown to reduce the TpTe interval in two recent studies 28,29 . Our study also found a significant reduction in the TpTe interval with LBBP‐CRT.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…A prolonged TpTe interval and TpTe/QT ratio have been shown to be associated with arrhythmogenesis and sudden cardiac death 30 . LBBP‐CRT has been shown to reduce the TpTe interval in two recent studies 28,29 . Our study also found a significant reduction in the TpTe interval with LBBP‐CRT.…”
Section: Discussionsupporting
confidence: 73%
“…30 LBBP-CRT has been shown to reduce the TpTe interval in two recent studies. 28,29 Our study also found a significant reduction in the TpTe interval with LBBP-CRT.…”
Section: Repolarization Parameterssupporting
confidence: 72%
See 2 more Smart Citations
“…These studies have shown that increased values of these postprocedural parameters are associated with a higher risk of malignant ventricular arrhythmia occurrence due to the inhomogeneity of myocardial repolarization between different parts or layers of the myocardium creating the basis for arrhythmogenesis. Recent data have shown that LBBAP improved the dispersion of repolarization in heart failure patients, and this improvement was associated with positive echocardiographic response [ 11 ].…”
Section: Introductionmentioning
confidence: 99%